Late Pleistocene sedimentary history of multiple glacially dammed lake episodes along the Yarlung-Tsangpo river, southeast Tibet. Issue 2 (September 2014) - Huang, Shao-Yi; Chen, Yue-Gau; Burr, George S.; Jaiswal, Manoj K.; Lin, Yunung Nina; Yin, Gongming; Liu, Jingwei; Zhao, Shujun; Cao, Zhongquan
Abstract: We present a reconstructed lithologic column compiled from a series of lacustrine outcrops along a tributary of the Nyang River, a major tributary of the Yarlung-Tsangpo in southeast Tibet. The deposits were preserved between terraces at altitudes of 2950–3100 m asl. The stratigraphic record features at least two sets of coarsening-upward sequences depicting episodic aggradation and progradation of a glacially dammed lake related delta. Recognized facies changes illustrate the evolution cycles of depositional environments from pro-delta, delta front, to delta plain. Radiocarbon and optically stimulated luminescence dates reveal an aging-downward trend in stratigraphic order and provide an approximate timeline for the formation of glacially dammed lakes in late Pleistocene. This result reflects that the Zelunglung Glacier had progressively advanced to block the Yarlung-Tsangpo river and the dam materials had stepwise stacked up to an altitude of 3095 m asl during Marine Oxygen Isotope Stages 4 to 2.